Gait analysis of goat at different slopes and study on biomimetic walking mechanism - Fu, Zhang; Wei, Wang; Guoying, Zhang; Jun, Wang; Zhaomei, Qiu; Pengjun, Mao (International Journal of Agricultural and Biological Engineering, 2016)
To study the walking status of a goat on slope and the walking mechanics, a comparative analysis of the walking gait mode of a goat on different slopes was conducted. The uphill and downhill walking processes on different slopes (6°, 18° and 36°) were recorded by a high speed video system. The experimental image results were processed and analyzed via SigmaScan software and MATLAB software. The characteristic parameters of locomotion gait on the different slopes and the angle change curves of each goat leg in the process of slope movement indicated that the goat performed tetrapod gait, static gait, ipsilateral gait and trot gait on different slopes. With the increase of gradient in the uphill process, the corresponding load factors of each leg were 0.65±0.15, 0.75 and 0.645±0.205, whereas those in the downhill process were 0.70±0.08, 0.66±0.06, and 0.685±0.125. Results showed that the load factors of each leg are higher than 0.5. The foreleg angle of  (the angle of wrist joints), which ranges from 100° to 130°, is suitable for different slopes. However, the angle of  (the angle between the thigh and the forward direction in the walking process of goat), which ranges from 99° to 109°, is suitable for the 6° slope, whereas the angle ranging from 46° to 91° is suitable for the 18° slope and 36° slope. For the hind leg, the angle of , which ranges from 105° to 153°, is suitable for the different slopes. The angle of , which ranges from 128° to 150°, is suitable for the different slopes. The research can provide a theoretical basis and experimental data for the design of biomimetic agricultural slope walking mechanism.Keywords: biomimetic walking, goat gait, slope walking mechanism, agricultural robot, SigmaScan, MATLABDOI: 10.3965/j.ijabe.20160903.2260Citation: Zhang F, Wang W, Zhang G Y, Wang J, Qiu Z M, Mao P J. Gait analysis of goat at different slopes and study on biomimetic walking mechanism. Int J Agric & Biol Eng, 2016; 9(3): 40－47.